2013
DOI: 10.3892/ol.2013.1470
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of hepatocellular carcinoma growth by adenovirus-mediated expression of human telomerase reverse transcriptase COOH-27 terminal polypeptide in mice

Abstract: A 27-kDa C-terminal fragment of human telomerase reverse transcriptase, hTERTC27, has previously been reported to inhibit the growth and tumorigenicity of HeLa human cervical cancer cells and U87-MG human glioblastoma multiforme cells. However, the antitumor effects of hTERTC27 in hepatoma and its underlying mechanisms are unclear. In the current study, the therapeutic effect of hTERTC27, mediated by recombinant adenovirus, in hepatocellular carcinoma (HCC) was explored in vitro and in vivo to investigate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
(27 reference statements)
1
6
0
Order By: Relevance
“…A single dose of 5 Â 10 7 plaque-forming units (PFU) rAd5-hTERTC27 administered intravenously into mice also inhibited the growth of HCC significantly. Furthermore, we confirmed that both telomerase-based gene regulation and regulation of the immune system played important roles in the antitumor effect of hTERTC27 on HCC (He et al, 2013).…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…A single dose of 5 Â 10 7 plaque-forming units (PFU) rAd5-hTERTC27 administered intravenously into mice also inhibited the growth of HCC significantly. Furthermore, we confirmed that both telomerase-based gene regulation and regulation of the immune system played important roles in the antitumor effect of hTERTC27 on HCC (He et al, 2013).…”
Section: Introductionsupporting
confidence: 79%
“…SD rats are advantageous because of their steady response to drugs, clear genetic background, and small individual variability, while Cynomolgus monkeys are extremely beneficial because they are physiologically similar to human beings. Having performed the initial, preclinical studies on the pharmacodynamics, safety pharmacology and acute toxicology of rAD5-hTERTC27 (He et al, 2013;Yue et al, 2013). We are now investigating its potential longer-term toxicological effects and immunogenicity following repeated intravenous dosing in rats and monkeys.…”
Section: Introductionmentioning
confidence: 98%
“…10 Abdul-Ghani et al 11 reported that hTERT expressed in more than 80% of HCC cells and suggested that telomere elongation is a potential target of gene therapy for HCC. Previous study reported that adenovirus-mediated expression of hTERT COOH-27 terminal polypeptide inhibited HCC growth in mice 12 and overexpression of hTERTC27 also inhibited growth of HeLa cell and tumorigenicity in nude mouse xenografts. 13 In this study, we identified that human telomerase reverse transcriptase receptor (hTERTR) could interact with hTERT and disorder cellular metabolism of HCC cells.…”
Section: Introductionmentioning
confidence: 99%
“…Although the function of COOH terminus is the least-characterized, it has been found to mediate the nuclear translocation of telomerase (13) and is essential for the in vivo activity of human telomerase (14). Recent studies showed that ectopic expression of C27 (amino acid 882-1,132 of hTERT) reduces the growth and tumorigenicity of tumor cells (15)(16)(17)(18)(19) and sensitizes tumor cells to 5-fluorouracil-induced growth inhibition and apoptosis (20). C27 does not affect telomerase activity.…”
Section: Introductionmentioning
confidence: 99%
“…C27 does not affect telomerase activity. The unclearly illustrated mechanisms include the induction of telomere dysfunction (15), triggering of apoptosis signal and reduction of angiogenesis in tumor tissue (16), as well as involvement of immune responses (18).…”
Section: Introductionmentioning
confidence: 99%